Impairment of Lhca4, a subunit of LHCI, causes high accumulation of chlorophyll and the stay-green phenotype in rice. (3rd January 2018) - Yamatani, Hiroshi; Kohzuma, Kaori; Nakano, Michiharu; Takami, Tsuneaki; Kato, Yusuke; Hayashi, Yoriko; Monden, Yuki; Okumoto, Yutaka; Abe, Tomoko; Kumamaru, Toshihiro; Tanaka, Ayumi; Sakamoto, Wataru; et al.
Abstract : Impairment of Lhca4, a subunit of LHCI, causes high chlorophyll content and LHCII accumulation in rice, suggesting a novel functional interaction between LHCI and LHCII. Abstract: Chlorophyll is an essential molecule for acquiring light energy during photosynthesis. Mutations that result in chlorophyll retention during leaf senescence are called 'stay-green' mutants. One of the several types of stay-green mutants, Type E, accumulates high levels of chlorophyll in the pre-senescent leaves, resulting in delayed yellowing. We isolated delayed yellowing1-1 ( dye1-1 ), a rice mutant whose yellowing is delayed in the field. dye1-1 accumulated more chlorophyll than the wild-type in the pre-senescent and senescent leaves, but did not retain leaf functionality in the 'senescent green leaves', suggesting that dye1-1 is a Type E stay-green mutant. Positional cloning revealed that DYE1 encodes Lhca4, a subunit of the light-harvesting complex I (LHCI). In dye1-1, amino acid substitution occurs at the location of a highly conserved amino acid residue involved in pigment binding; indeed, a severely impaired structure of the PSI-LHCI super-complex in dye1-1 was observed in a blue native PAGE analysis. Nevertheless, the biomass and carbon assimilation rate of dye1-1 were comparable to those in the wild-type. Interestingly, Lhcb1, a trimeric LHCII protein, was highly accumulated in dye1-1, in the chlorophyll–protein complexes. The high accumulation of LHCII in the LHCI mutant dye1 suggests a novel functional interaction between LHCI and LHCII.